Biocathode electrochemical activity and reduction characteristics of Cr(VI) system in microbial fuel cells. Issue 6 (25th March 2023) - Zhang, Wusheng; Zhao, Yu; Wang, Xiaxia; Ma, Xuli; Jin, Lie; Wang, Haicheng; Li, Hui; Yan, Jinbin; Pan, Weibin; Chen, Shuwei
Abstract: BACKGROUND: The biocathode of microbial fuel cells (MFCs) offers a simple method for the reductive treatment of Cr(VI), and Cr(VI) is an electron acceptor in cathodes in MFCs. In this study, MFCs with different Cr(VI) contents (7.07–35.35 mg L −1 ) were considered to evaluate the overall performance of MFCs. RESULTS: The results of electrochemical analysis confirmed that the MFC‐2 biocathode exhibited a higher effective reaction surface, stronger conductivity, and smaller charge transfer resistance (53.63 Ω) than the others. In addition, Cr(VI) had a power output of 75.6 mW m −2 in MFC‐2 and a Cr(VI) cathodic coulombic efficiency of 103.8%. With 14.14 mg L −1 Cr(VI) content, the cathode microbe had the best activity. Cr(VI) reduction followed a pseudo‐first‐order kinetic model, with the rate constant being 0.0139 h −1 . Meanwhile, this study analyzed the Cr(VI) reduction in MFCs and the release and acceptance of electrons and protons. Electrically active bacteria such as Proteobacteria were highly enriched on the anode and cathode biofilm, while the Cr(VI)‐reducing bacteria Gammaproteobacteria increased in the biofilm of the cathode. CONCLUSION: This study helps in the selection of Cr(VI) concentration for the cathode, guaranteeing microbial activity and power generation performance. Microbes have the best electrochemical activity in MFC‐2 (14.14 mg L −1 ). Meanwhile, the change in anode microbial activity was affected by cathode performance. The microbial community was significantly influenced by Cr(VI). © 2023 Society of Chemical Industry (SCI).